PERANCANGAN FILM PENDEK BERJUDUL SI AYU SEBAGAI MEDIA SOSIALISASI DAMPAK PSIKOLOGIS BODY SHAMING BAGI REMAJA PUTRI - Michael Bezaleel; Felicia Felicia (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2021)
Body shaming is known as the action of expressing humiliation by commenting, mocking, or criticizing about another individual’s body shape or size. This act is often considered a joke for many people, especially among teenagers, without realizing that it can cause mental problems for victims who receive this body shaming treatment. This form of bullying can cause the victim to lack confidence, low self-esteem and even suicide. Based on the background of the problems explained, creating an audio visual in the form of short film is judged as fit to be a relevant socialization media in this modern society. This research is using qualitative methodology, collecting datas by interviewing a number of sources and target audiences. Based on the results of data collection, this short film was designed with an emphasis on one of the psychological impacts experienced by the victim which is low self-esteem. As a result, this short film has presented a visualization that can convey messages about the psychological impact that occurs on victims of body shaming to teenage girls.